Subject Matter Expert Nurses in Safe Sleep Program Implementation. Issue 6 (November 2022) - Stringer, Marilyn; Ohnishi, Bonnie Renner; Ferrarello, Deborah; Lazzeri, Jessica; Giordano, Nicholas A.; Polomano, Rosemary C.
Abstract: Background: Pennsylvania sudden unexpected infant death rates rank among the highest nationally. A nursing team developed, implemented, evaluated, and disseminated an evidence-based quality improvement (QI) program at birthing hospitals in Pennsylvania to address this issue. To facilitate implementation, clinical nurses were educated as Subject Matter Experts (SMEs) to empower them to transform and sustain outcomes-driven QI for infant safe sleep nursing practice. Methods: This descriptive study examined outcomes from 268 nurses who received comprehensive education on infant safe sleep and the SME role. Likert-type scale surveys measured knowledge gained and progress made in practice following education. A programmatic dashboard tracked program implementation. Descriptive statistics were used to report findings. Intervention: SME nurses ( N = 268) completed two interactive learning modules addressing safe sleep guidelines and teaching strategies and attended a workshop to acquire skills for program implementation. Key competencies included data collection and dissemination, policy development, and communication techniques. Results: Immediate posteducation surveys completed by SMEs indicated that over 98% of respondents strongly agreed or agreed they were able to effectively demonstrate communication strategies, identify SME role components, provide environment surveillance, and demonstrate best practices in infant safe sleep. To allow time for assimilation of the of SME role, a survey was initiated at 6 months to capture progress made. Seventy-eight SMEs responded to the survey and reported exceptional or substantial progress in 10 areas for SME responsibilities. Conclusion: Use of the SME role for program implementation led to highly favorable SME-reported outcomes in leading a hospital-based QI program. Abstract : In this quality improvement project, maternity and neonatal nurses in hospitals in Pennsylvania particpated in a safe infant sleep program. After education, they became safe sleep subject matter experts who were knowledgeable, highly respected, expert communicators and collaborators committed to achieving high performance standards, and skilled in the evaluation, measurement, and dissemination of outcomes. They felt their education had prepared them to conduct data collection, synthesis, and dissemination activities associated with infant sleep safety.